A boron-containing quantum dot composite aggregate and its preparation method and application

By forming a stable three-coordination and four-coordination complex with boron-containing compounds with quantum dots, the problem of poor stability of quantum dots at high temperatures is solved, and high stability and heat resistance in LCD and other applications are achieved, avoiding The appearance of black and yellow dots.

CN118546671BActive Publication Date: 2024-12-27CANNANO JIAYUAN (GUANGZHOU) SCI & TECH CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411020147.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-29
Publication Date
2024-12-27
Estimated Expiration
2044-07-29

Smart Images

  • Figure CN118546671B_ABST
    Figure CN118546671B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of quantum dots, and specifically relates to a boron-containing quantum dot complex aggregate and a preparation method and application thereof, comprising a tri-coordinate boron-containing quantum dot complex and a tetra-coordinate boron-containing quantum dot complex formed by chemical bonding of a boron-containing compound and a quantum dot that conform to formulas one and two, wherein the boron-containing compound in the tri-coordinate boron-containing quantum dot complex is covalently bonded to the quantum dot, and the boron-containing compound in the tetra-coordinate boron-containing quantum dot complex is coordinated to the quantum dot, and the ratio of the sum of the number of X-B covalent bonds and X-B coordination bonds in the boron-containing quantum dot complex aggregate is 0.10%-50%. The boron-containing quantum dot complex of the present invention can take into account strong binding ability and oxidation resistance, has good heat resistance, is conducive to improving the stability of quantum dots, and simultaneously ensures excellent optical properties, effectively avoiding the occurrence of black and yellow spots.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of quantum dots, and in particular relates to a boron-containing quantum dot complex aggregate and a preparation method and application thereof. Background Art

[0002] Quantum dots (QDs) are a type of crystalline nanoparticles that exhibit size-dependent properties due to the quantum confinement effect of the electronic state. Due to their excellent luminescence properties (adjustable emission wavelength, high quantum yield, narrow and symmetrical emission spectrum), they have broad application prospects in the fields of display, lighting, solar energy and biomedicine. At present, the application of quantum dot photoluminescence technology in LCD liquid crystal display backlights has gradually matured, and different embedding solutions such as QD on chip, QD on edge, QD on surface and QD on plate have been developed for a variety of backlight structures. However, the stability of quantum dots is still one of the main obstacles to their application in LCDs.

[0003] Quantum dots are usually composed of an inorganic core-shell or bare core and surface ligands. As a nanomaterial (particle size is generally between 1-30nm), due to its large specific surface area, surface atoms can easily react with water and oxygen to form defects, causing a significant decrease in the fluorescence of quantum dots. The surface ligands of quantum dots bind to the inorganic surface of the quantum dots, reducing the number of surface defect states caused by dangling bonds, while providing colloidal stability of the quantum dots. Therefore, the surface ligands of quantum dots play a leading role in maintaining the colloidal properties of quantum dots and passivating surface defects of quantum dots.

[0004] The ligands on the surface of quantum dots can be divided into three types (Owen J. The coordination chemistry of nanocrystal surfaces. Science, 2015, 347: 614-615): such as L-type ligands (RNH2 and PR3 types that provide two lone pairs of electrons), X-type ligands (carboxylates, phosphates and Cl groups that provide one lone pair of electrons). –etc.) and Z-type ligands (long-chain carboxylates or phosphonates that can accept lone pairs of electrons), (Z. Hens. From ligands to binding motifs and beyond; the enhanced versatility of nanocrystal surfaces. Dalton Trans., 2016, 45, 13277-13283). It is generally believed that quantum dot L-type ligands and X-type ligands bind to cations on the surface of quantum dots to protect metal cations (such as Zn, Cd, etc.); Z-type ligands act as electron acceptors and bind to anions to protect anions (such as Se, S, etc.). Nicholas Kirkwood et al., Journal of the American Chemical Society 2018 140(46), 15712-15723 found that the increase in band gap energy levels caused by surface states is the main reason affecting the optical and electronic properties of quantum dots. The defect states of group II-VIA and group III-VA quantum dots are mainly caused by anions on the surface of quantum dots. The use of Z-type ligands (Lewis acids) can well passivate the defect states caused by anions, thereby improving the PLQY of quantum dots. Rahul Singh et al., ACS Applied Nano Materials 2022 5 (12), 18014-18022 found that the use of Z-type ligands (ZnCl2, CdCl2, etc.) to treat the surface of CdSe / ZnS gradient alloy core-shell quantum dots confirmed that the Z-type ligands passivated the defect states of quantum dots by bonding with unsaturated sulfur atoms on the surface, and their PLQY and optical stability were significantly improved.

[0005] At present, the strategy of using Z-type ligands to improve the optical properties and stability of quantum dots has become an indispensable means in the field of quantum dot applications. For example: US20190031952A1, CN110205111A use organic zinc thiolate and metal thiolate to improve the optical properties and stability of quantum dot complexes and their devices; CN115181561A uses metal carboxylates and metal phosphonates to improve the stability of quantum dot complexes and their devices; CN112480927A uses metal halides and organic ligands to improve the stability of quantum dot materials; CN113366083A uses Z-type ligand ZnCl2 to improve the optical properties and stability of quantum dot materials; CN113710773A uses zinc dioleate and metal halides to improve the quantum yield of InP quantum dots; CN114341312A uses zinc acetate and zinc fluoride to treat InP / ZnSe, InP / ZnSe / ZnS quantum dots, achieving the improvement of their optical properties and stability.

[0006] The above patented technologies all use metal salts, especially organic metal salts (mostly zinc salts) Z-type ligands and their complexes to enhance the optical properties and stability of quantum dots. However, the use of such Z-type ligands has certain limitations, such as: organic thiolates are not heat resistant enough (<200°C) and are not suitable for high temperature (210°C-270°C) melt extrusion processing of quantum dot diffusion plates; organic carboxylates and organic phosphonates have poor dispersion in the processing of PS quantum dot diffusion plates, and are prone to produce black and yellow spots on the plate surface.

[0007] Although quantum dots using boron-containing compounds as ligands have appeared in the prior art, their optical properties and stability have not been studied in depth, making it difficult to meet the requirements of optical diffusion plates for the high stability and heat resistance of quantum dots.

[0008] It should be noted that this part of the present invention only provides background technology related to the present invention and does not necessarily constitute prior art or known technology. Summary of the invention

[0009] The purpose of the present invention is to overcome the defects of the existing quantum dot complexes in the prior art, namely, poor stability and heat resistance, and to provide a boron-containing quantum dot complex aggregate and a preparation method and application thereof. The boron-containing quantum dot complex can take into account strong binding ability and oxidation resistance, good heat resistance, and is conducive to improving the stability of quantum dots, while ensuring excellent optical properties and effectively avoiding the appearance of black and yellow spots.

[0010] In order to achieve the above-mentioned object, in a first aspect, the present invention provides a boron-containing quantum dot complex aggregate, comprising a tri-coordinate boron-containing quantum dot complex and a tetra-coordinate boron-containing quantum dot complex formed by chemical bonding of a boron-containing compound and a quantum dot, wherein the boron-containing compound in the tri-coordinate boron-containing quantum dot complex is covalently bonded to the quantum dot, and the boron-containing compound in the tetra-coordinate boron-containing quantum dot complex is coordination-bonded to the quantum dot, and the ratio of XB coordination bonds in the boron-containing quantum dot complex aggregate to the sum of the number of XB covalent bonds and XB coordination bonds is 0.10%-50%, and X is selected from X1, X2, X3, X4, X5, and X6; wherein the chemical general formula of the tri-coordinate boron-containing quantum dot complex is as follows: Formula 1, and the chemical general formula of the tetra-coordinate boron-containing quantum dot complex is as follows: Formula 2;

[0011] Formula 1; Formula 2;

[0012] Wherein, QD is quantum dot; R8, R9, R 10 , R 11 , R 12 , R 13Each of them is independently selected from alkoxy, hydrocarbon, substituted hydrocarbon, halogen, carboxyl, hydroxyl, aldehyde, ester and amide, and the substituent in the substituted hydrocarbon is selected from at least one of halogen, hydroxyl, alkoxy, carboxyl, aldehyde, ester and amide; n1=natural number, n2=natural number; X1, X2, X3, X4, X5 and X6 are each independently selected from VIA group elements, VA group elements and IVA group elements.

[0013] In some preferred embodiments of the present invention, the boron-containing quantum dot complex aggregate is a boron-containing quantum dot dispersion, and the content of boron in the boron-containing quantum dot dispersion is 1000ppm-9000ppm.

[0014] In some preferred embodiments of the present invention, the boron-containing quantum dot composite aggregate is a boron-containing quantum dot composite plate, and the content of boron element in the boron-containing quantum dot composite plate is 13ppm-1750ppm.

[0015] In some preferred embodiments of the present invention, X1, X2, X3, X4, X5, and X6 are each independently selected from O, S, Se, Te, N, P, As, C, Si, and Ge.

[0016] In some preferred embodiments of the present invention, R8, R9, R 10 , R 11 , R 12 , R 13 Each of them is independently selected from an alkoxy group having 1-18 carbon atoms, a hydrocarbon group having 1-18 carbon atoms, a substituted hydrocarbon group having 1-18 carbon atoms, a halogen, a carboxyl group, a hydroxyl group, an aldehyde group, an ester group, and an amide group; the hydrocarbon group having 1-18 carbon atoms is selected from an alkyl group having 1-18 carbon atoms, an aryl group having 6-18 carbon atoms, an alkenyl group having 2-18 carbon atoms, and an alkynyl group having 2-18 carbon atoms.

[0017] In some preferred embodiments of the present invention, R8, R9, R 10 , R 11 , R 12 , R 13 Each of them is independently selected from an alkoxy group having 1-18 carbon atoms, an alkyl group having 1-18 carbon atoms, an aryl group or a substituted aryl group having 6-18 carbon atoms, and a hydroxyl group; wherein the substituent group in the substituted aryl group having 6-18 carbon atoms is selected from at least one of an alkyl group, a halogen group, a hydroxyalkyl group, an alkoxy group, a halogen group, a carboxyl group, and an aldehyde group.

[0018] In some preferred embodiments of the present invention, the tri-coordinate boron-containing quantum dot complex is selected from:

[0019] , , , , , , , , At least one of .

[0020] In some preferred embodiments of the present invention, the tetracoordinate boron-containing quantum dot complex is selected from:

[0021] , , , , , , , , At least one of .

[0022] In some preferred embodiments of the present invention, the quantum dots are of a bare core structure, and the surface of the bare core structure has at least one of Group IVA atoms, Group VA anions, and Group VIA anions.

[0023] In some preferred embodiments of the present invention, the quantum dots are of a core-shell structure, and the shell surface of the core-shell structure contains at least one of Group IVA atoms, Group VA anions, and Group VIA anions.

[0024] In a second aspect, the present invention provides a method for preparing a boron-containing quantum dot dispersion, comprising the following steps:

[0025] S1. Prepare a boron-containing compound and a dispersing solvent;

[0026] S2, adding quantum dots into a system of boron-containing compounds and a dispersing solvent and introducing an inert gas;

[0027] S3, heating, mixing and dispersing the system obtained in S2, and keeping the temperature for reaction; during the reaction, the boron-containing compound reacts with the quantum dots to form a tri-coordinate boron-containing quantum dot complex and a tetra-coordinate boron-containing quantum dot complex, the boron-containing compound in the tri-coordinate boron-containing quantum dot complex is covalently bonded to the quantum dots, and the boron-containing compound in the tetra-coordinate boron-containing quantum dot complex is coordination-bonded to the quantum dots, the ratio of XB coordination bonds in the boron-containing quantum dot dispersion to the sum of the number of XB covalent bonds and XB coordination bonds is 0.10%-50%, and X is selected from X1, X2, X3, X4, X5, and X6;

[0028] S4, cooling;

[0029] In S3, the chemical formula of the tri-coordinate boron-containing quantum dot complex is as shown in the following formula 1, and the chemical formula of the tetra-coordinate boron-containing quantum dot complex is as shown in the following formula 2;

[0030] Formula 1; Formula 2;

[0031] Wherein, QD is quantum dot; R8, R9, R 10 , R 11 , R 12 , R 13 Each of them is independently selected from alkoxy, hydrocarbon, substituted hydrocarbon, halogen, carboxyl, hydroxyl, aldehyde, ester and amide, the substituent in the substituted hydrocarbon is selected from at least one of halogen, hydroxyl, alkoxy, carboxyl, aldehyde, ester and amide, n1=natural number, n2=natural number, X1, X2, X3, X4, X5 and X6 are each independently selected from VIA group elements, VA group elements and IVA group elements.

[0032] In some preferred embodiments of the present invention, the content of boron in the boron-containing quantum dot dispersion is 1000 ppm-9000 ppm.

[0033] In some preferred embodiments of the present invention, in S2, the mass ratio of quantum dots to boron-containing compounds is 1:0.25-5, and / or, the mass ratio of boron-containing compounds to dispersing solvent in S1 is 0.01-0.5:1.

[0034] In some preferred embodiments of the present invention, the dispersing solvent in S1 includes at least one of alkanes, aromatic hydrocarbons, organic amines, octadecene, organic carboxylic acids containing 1 to 18 carbon atoms, liquid paraffin, acrylates, organic silanes, and organic phosphines.

[0035] In some preferred embodiments of the present invention, the reaction temperature of the insulation reaction in S3 is higher than the melting point of the boron-containing compound and the dispersion solvent system and lower than the boiling point of the boron-containing compound and the dispersion solvent system, the reaction time is 0.1h-3h, and the stirring speed of the mixed dispersion is 100 rpm-300 rpm.

[0036] In some preferred embodiments of the present invention, when the ratio of covalent bonds needs to be increased, the reaction temperature in S3 is controlled to be 100°C-300°C; when the ratio of coordination bonds needs to be increased, the reaction temperature in S3 is controlled to be 30°C-100°C and not equal to 100°C;

[0037] In some preferred embodiments of the present invention, the quantum dots are of a core-shell structure or a bare core structure, and the quantum dots are in the form of a solid or a concentrated solution, and the mass fraction of the solid content of the quantum dots in the concentrated solution is 5%-50%.

[0038] In some preferred embodiments of the present invention, the boron-containing compound comprises at least one of the corresponding compounds of the following three general formulae and their dehydration condensation, esterification, and amidation derivative compounds:

[0039] General formula 1, , R1, R2, and R3 are each independently selected from a hydrocarbon group, an alkoxy group, a halogen group, and a substituted hydrocarbon group;

[0040] General formula 2: , R4 and R5 are each independently selected from carboxyl, substituted hydrocarbon, halogen, hydrocarbon, alkoxy, and hydroxyl;

[0041] General formula three: , R6 is selected from H or selected from hydrocarbon group, substituted hydrocarbon group, halogen, aldehyde group, carboxyl group, R7 is selected from hydrocarbon group, alkoxy group, hydroxyalkyl group, hydroxyl group;

[0042] In the three general formulas, the substituents in the substituted hydrocarbon group are independently selected from at least one of halogen, hydroxyl, alkoxy, carboxyl, aldehyde, ester and amide.

[0043] In some preferred embodiments of the present invention, the boron-containing compound comprises at least Formula 3.

[0044] In some preferred embodiments of the present invention, the number of carbon atoms in any carbon-containing group in Formula 1, Formula 2, and Formula 3 is less than 18, wherein the hydrocarbon group is selected from alkyl, aryl, alkenyl, and alkynyl.

[0045] In a third aspect, the present invention provides a boron-containing quantum dot dispersion liquid, which is prepared by the preparation method of the boron-containing quantum dot dispersion liquid described in the second aspect.

[0046] In a fourth aspect, the present invention provides a method for preparing a boron-containing quantum dot composite plate, comprising the following steps:

[0047] S101, provide boron-containing compounds, quantum dot concentrates, polymer granules, and sheet functional additives;

[0048] S102, mixing the quantum dot concentrate with at least part of the polymer pellets to obtain a quantum dot polymer mixture;

[0049] S103, melt-extrude the quantum dot polymer mixture, the boron-containing compound, and the plate functional additive to form a boron-containing quantum dot composite plate; during the process, the boron-containing compound reacts with the quantum dots to form a tri-coordinate boron-containing quantum dot composite and a tetra-coordinate boron-containing quantum dot composite, the boron-containing compound in the tri-coordinate boron-containing quantum dot composite is covalently bonded to the quantum dots, and the boron-containing compound in the tetra-coordinate boron-containing quantum dot composite is coordination-bonded to the quantum dots, and the ratio of XB coordination bonds to the sum of the number of XB covalent bonds and XB coordination bonds in the boron-containing quantum dot composite plate is 0.10%-50%, and X is selected from X1, X2, X3, X4, X5, and X6;

[0050] In S103, the chemical formula of the tri-coordinate boron-containing quantum dot complex is as shown in the following formula 1, and the chemical formula of the tetra-coordinate boron-containing quantum dot complex is as shown in the following formula 2;

[0051] Formula 1; Formula 2;

[0052] Wherein, QD is quantum dot; R8, R9, R 10 , R 11 , R 12 , R 13 Each of them is independently selected from alkoxy, hydrocarbon, substituted hydrocarbon, halogen, carboxyl, hydroxyl, aldehyde, ester and amide, the substituent in the substituted hydrocarbon is selected from at least one of halogen, hydroxyl, alkoxy, carboxyl, aldehyde, ester and amide, n1=natural number, n2=natural number, X1, X2, X3, X4, X5 and X6 are each independently selected from VIA group elements, VA group elements and IVA group elements.

[0053] In some preferred embodiments of the present invention, the content of boron in the boron quantum dot composite plate is 13ppm-1750ppm.

[0054] In some preferred embodiments of the present invention, the mass ratio of quantum dots to the total amount of boron-containing compounds is 1:0.5-40, and the mass of the boron-containing compounds used for coordination and bonding with other lone pairs of electrons or conjugated electron donors in the raw materials other than quantum dots is 1.2%-1000% of the mass of the quantum dots.

[0055] In some preferred embodiments of the present invention, the melt extrusion process of S103 includes: subjecting the boron-containing compound, antioxidant, light stabilizer, and another part of the polymer pellets to a second mixed extrusion to obtain auxiliary agent pellets; then, the quantum dot polymer mixture and the auxiliary agent pellets are fed into a first extruder, and the diffusant and the toughening agent are respectively fed into a second extruder and a third extruder, and then melt extruded; wherein the temperature of the second mixed extrusion is 180°C-220°C.

[0056] In some preferred embodiments of the present invention, the conditions of the melt extrusion in S103 include: a processing temperature of 210° C.-270° C., and a reaction time of 1-2 min.

[0057] In some preferred embodiments of the present invention, the stirring speed of the first mixing in S102 is 300-700 rpm.

[0058] In some preferred embodiments of the present invention, the boron-containing quantum dot composite plate is a boron-containing quantum dot optical diffusion plate, and the corresponding plate functional additives include at least one of an antioxidant, a light diffuser, a toughening agent, and a light stabilizer; the quantum dots include red quantum dots and / or green quantum dots, and the polymer particles are selected from polystyrene, polymethyl methacrylate, polycarbonate, polyethylene, and polypropylene.

[0059] Further preferably, the thickness of the boron quantum dot-containing composite plate is 1.2 mm-3.0 mm.

[0060] Further preferably, in S101, based on the total amount of raw materials, the mass fraction of the boron-containing compound is 0.05%-1%, the mass fraction of the quantum dot concentrate is 0.05%-0.2%, the mass fraction of the quantum dots in the quantum dot concentrate is 5%-50%, the mass fraction of the antioxidant is 0.1%-2%, the total mass fraction of the light diffuser and the toughening agent is 0.5%-2%, and the mass fraction of the light stabilizer is 0.05%-2%.

[0061] In some preferred embodiments of the present invention, the boron-containing compound comprises at least one of the corresponding compounds of the following three general formulae and their dehydration condensation, esterification, and amidation derivative compounds:

[0062] General formula 1, , R1, R2, and R3 are each independently selected from a hydrocarbon group, an alkoxy group, a halogen group, and a substituted hydrocarbon group;

[0063] General formula 2: , R4 and R5 are each independently selected from carboxyl, substituted hydrocarbon, halogen, hydrocarbon, alkoxy, and hydroxyl;

[0064] General formula three: , R6 is selected from H or selected from hydrocarbon group, substituted hydrocarbon group, halogen, aldehyde group, carboxyl group, R7 is selected from hydrocarbon group, alkoxy group, hydroxyalkyl group, hydroxyl group;

[0065] In the three general formulas, the substituents in the substituted hydrocarbon group are independently selected from at least one of halogen, hydroxyl, alkoxy, carboxyl, aldehyde, ester and amide.

[0066] In some preferred embodiments of the present invention, the boron-containing compound comprises at least Formula 3.

[0067] In some preferred embodiments of the present invention, the number of carbon atoms in any carbon-containing group in Formula 1, Formula 2, and Formula 3 is less than 18, wherein the hydrocarbon group is selected from alkyl, aryl, alkenyl, and alkynyl.

[0068] In a fifth aspect, the present invention provides a boron-containing quantum dot composite plate, which is prepared by the preparation method of the boron-containing quantum dot composite plate described in the fourth aspect.

[0069] In a sixth aspect, the present invention provides an application of the boron-containing quantum dot complex aggregate described in the first aspect in a quantum dot diffusion plate, a quantum dot light-converting agricultural film, a quantum dot on-chip package, and a quantum dot electroluminescent device.

[0070] Beneficial effects:

[0071] The present invention forms a tri-coordinate boron-containing quantum dot complex and a tetra-coordinate boron-containing quantum dot complex with an appropriate boron content through the above technical scheme, especially through the quantum dots stabilized by boron-containing compounds. Since the number of valence orbitals (4) of boron is greater than the number of valence bond electrons (3), boron mainly forms a neutral compound with sp2 Hybridization forms a planar triangular three-coordinate boron-containing quantum dot complex and retains an empty p orbital, which makes the three-coordinate boron compound have obvious electron deficiency and is easily attacked by electron-rich groups to form a four-coordinate boron-containing quantum dot complex. Therefore, the boron compound can be used as a Z-type ligand to bind to the surface anions of the quantum dots to form a more stable protection for them. The boron compound has good heat resistance and ensures excellent optical properties, effectively avoiding the appearance of black and yellow spots; and controlling the ratio of XB coordination bonds in the aggregates of the boron-containing quantum dot complex to the sum of the number of XB covalent bonds and XB coordination bonds within a suitable range, which can make full use of the strong binding ability of the three-coordinate boron-containing quantum dot complex and the strong oxidation resistance of the four-coordinate boron-containing quantum dot complex, which is more conducive to taking into account the strong binding ability and oxidation resistance, better heat resistance and stability, longer life, and further effectively avoiding the appearance of black and yellow spots.

[0072] Compared with the quantum dot complexes of the prior art, the present invention significantly improves the stability of quantum dots. The essential principle is that boron-containing compounds (especially electron-deficient tri-coordinate boron compounds) can be used as a ligand to protect quantum dot anions, and can form tri-coordinate boron-containing quantum dot complexes and tetra-coordinate boron-containing quantum dot complexes with appropriate boron content to achieve the effect of improving the stability of quantum dots. The present invention is applicable to a wide range of scenarios. In a homogeneous system, as long as the surface of the quantum dot is combined with the boron-containing compound provided by the present invention, no matter what form of application, the effect of improving stability can be achieved. In addition, the electron transmission and stability performance of quantum dot materials in electroluminescent applications can be improved.

[0073] In a preferred embodiment of the present invention, for boron-containing quantum dot complex aggregates in different forms, the mass content of the boron element is controlled within their respective appropriate ranges, which is beneficial to improving the stability of the quantum dots, allowing the boron-containing compounds to better and longer protect the optical properties of the quantum dots, further effectively avoiding the appearance of black and yellow spots. BRIEF DESCRIPTION OF THE DRAWINGS

[0074] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0075] Figure 1 The PLQY variation curves of quantum dot PS optical sheets prepared from green quantum dots obtained in some embodiments and comparative examples after aging for different time periods.

[0076] Figure 2 The PLQY variation curves of the quantum dot PS optical sheets prepared from the red quantum dots obtained in some embodiments and comparative examples after aging for different time periods.

[0077] Figure 3 The following are the curves showing the variation of the color coordinate x of the boron quantum dot optical diffuser plates obtained in some embodiments and comparative examples with different aging times.

[0078] Figure 4 The graphs are the variation curves of the color coordinate y of the boron quantum dot optical diffuser plates obtained in some embodiments and comparative examples with different aging times.

[0079] Figure 5 The graphs are the variation curves of Lv of the boron quantum dot optical diffuser plates obtained in some embodiments and comparative examples with different aging times. DETAILED DESCRIPTION

[0080] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Among them, the terms "optional" and "optional" all mean that they may be included or not included (or may be present or not).

[0081] In the first aspect, the present invention provides a boron-containing quantum dot complex aggregate, comprising a tri-coordinate boron-containing quantum dot complex and a tetra-coordinate boron-containing quantum dot complex formed by chemical bonding of a boron-containing compound and a quantum dot, wherein the boron-containing compound in the tri-coordinate boron-containing quantum dot complex is covalently bonded to the quantum dot, and the boron-containing compound in the tetra-coordinate boron-containing quantum dot complex is coordinated and bonded to the quantum dot, and the ratio of XB coordination bonds to the sum of the number of XB covalent bonds and XB coordination bonds in the boron-containing quantum dot complex aggregate is 0.10%-50%, and X is selected from X1, X2, X3, X4, X5, and X6. The present invention adopts a suitable proportion of coordination bonds and covalent bonds, which can take into account the stability of the boron-containing quantum dot complex aggregate while enhancing the protection of the anions on the surface of the quantum dots (wherein the tri-coordinate covalent bonding is more firm and the tetra-coordinate coordination bonding is more antioxidant), thereby facilitating the improvement of the stability and life of the quantum dot composite material.

[0082] In the present invention, the number of coordination bonds and covalent bonds can be obtained by molecular absorption spectrum detection. The positions of characteristic peaks of molecular spectrum (including BS covalent bonds and BS coordination bonds) can be found in chemical handbooks and will not be described in detail here. For example, in the molecular absorption spectrum, for example, the BO bond has a Raman spectrum vibration frequency of 700-900cm -1 The BO bond peaks at 1350-1310 cm in NMR and IR. -1 The coordination number can be determined by the boron atomic chemical shift using the boron nuclear magnetic resonance spectrum. Regardless of the method used to detect the number of coordination bonds and covalent bonds, the ratio of coordination bonds to covalent bonds in the present invention is within the range.

[0083] In the present invention, the ratio of XB coordination bonds to the sum of the number of XB covalent bonds and XB coordination bonds is 0.10%-50%. For example, the corresponding ratio can be 0.10%, 0.5%, 0.8%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, etc., and the range between any two point values, and further, for example, it can be preferably 8%-30%.

[0084] The general chemical formula of the tri-coordinate boron-containing quantum dot complex is as shown in the following formula 1, and the general chemical formula of the tetra-coordinate boron-containing quantum dot complex is as shown in the following formula 2;

[0085] Formula 1; Formula 2;

[0086] Wherein, QD is quantum dot; R8, R9, R 10 , R 11 , R 12 , R 13 Each of them is independently selected from alkoxy, hydrocarbon, substituted hydrocarbon, halogen, carboxyl, hydroxyl, aldehyde, ester and amide, the substituent in the substituted hydrocarbon is selected from at least one of halogen, hydroxyl, alkoxy, carboxyl, aldehyde, ester and amide, n1=natural number, n2=natural number, X1, X2, X3, X4, X5 and X6 are each independently selected from VIA group elements, VA group elements and IVA group elements.

[0087] In the present invention, "hydrocarbon group" includes alkyl, aryl, alkenyl, and alkynyl. "Substituted hydrocarbon group" refers to a group in which a hydrocarbon group selected from at least one of alkyl, aryl, alkenyl, and alkynyl is substituted with a substituent. Exemplarily, the hydrocarbon group with 1-18 carbon atoms is selected from alkyl with 1-18 carbon atoms, aryl with 6-18 carbon atoms, alkenyl with 2-18 carbon atoms, and alkynyl with 2-18 carbon atoms, and the substituted hydrocarbon group with 1-18 carbon atoms is selected from substituted alkyl with 1-18 carbon atoms, substituted aryl with 6-18 carbon atoms, substituted alkenyl with 2-18 carbon atoms, and substituted alkynyl with 2-18 carbon atoms. In the present invention, "carbon atoms of 1-18" means that the number of carbon atoms can be selected from 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, and 18. "The number of carbon atoms is 6-18" means that the number of carbon atoms can be selected from 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, and the same applies to the others. Of course, hydroxyalkyl is a substituted hydrocarbon group.

[0088] The quantum dots QD of the present invention can be specifically monodisperse quantum dot particles or quantum dot aggregates. As long as the surface of the quantum dots contains at least one of the VIA group elements, the VA group elements, and the IVA group elements, they can form a tri-coordinate boron-containing quantum dot complex and / or a tetra-coordinate boron-containing quantum dot complex. It can be understood that X1, X2, X3, X4, X5, and X6 are elements contained on the surface of the quantum dots QD, respectively, which can enable the quantum dots to be chemically bonded to the boron-containing compound.

[0089] Wherein, n1 and n2 are natural numbers, for example, independently 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 20, etc. The measured values ​​of n1 and n2 in the boron-containing quantum dot composite aggregate and the n1 and n2 calculated based on the theoretical values ​​of the raw material input are both natural numbers.

[0090] Preferably, n1 = 0-20, n2 = 0-20. The use of n1 and n2 in the appropriate preferred range can ensure the properties of the boron-containing quantum dot complex aggregate solution while enhancing the binding force between the boron-containing compound molecules and the quantum dot surface (more covalent or coordinated binding sites), thereby being more conducive to improving the dispersibility and stability of the boron-containing quantum dot complex aggregate.

[0091] In some preferred embodiments of the present invention, X1, X2, X3, X4, X5, and X6 are each independently selected from O, S, Se, Te, N, P, As, C, Si, and Ge.

[0092] In some preferred embodiments of the present invention, R8, R9, R 10 , R 11 , R 12 , R 13 They are independently selected from alkoxy groups with 1 to 18 carbon atoms, hydrocarbon groups with 1 to 18 carbon atoms, substituted hydrocarbon groups with 1 to 18 carbon atoms, halogen, carboxyl, hydroxyl, aldehyde, ester, and amide groups. The hydrocarbon group may be a straight-chain hydrocarbon group, a branched hydrocarbon group, or a cyclic hydrocarbon group. As long as the above ranges and the corresponding general structure and the corresponding coordination bond and covalent bond content are met, the effects of the present invention can be achieved.

[0093] More preferably, R8, R9, R 10 , R 11 , R 12 , R 13 Each is independently selected from an alkoxy group having 1 to 18 carbon atoms, an alkyl group having 1 to 18 carbon atoms, preferably 2 to 16 carbon atoms, an aryl group or a substituted aryl group having 6 to 18 carbon atoms, and a hydroxyl group.

[0094] It is further preferred that the substituent group in the substituted aryl group having 6 to 18 carbon atoms is selected from at least one of an alkyl group, a halogen group, a hydroxyalkyl group, an alkoxy group, a halogen group, a carboxyl group, and an aldehyde group.

[0095] The halogen in the present invention can be selected from fluorine, chlorine and bromine.

[0096] In some preferred embodiments, the boron-containing quantum dot complex aggregate is a boron-containing quantum dot composite plate, and R8, R9, R 10 , R 11 , R 12 , R 13 The halogen contained is fluorine. The preferred solution of the present invention can ensure the stability of quantum dots and excellent optical properties, and can also effectively avoid the occurrence of black and yellow dots.

[0097] In some preferred embodiments of the present invention, the boron-containing quantum dot complex aggregate is a boron-containing quantum dot dispersion, and R8, R9, R 10 , R 11 do not contain phenyl at the same time; and / or, R8 and R9 are not halogen at the same time, and R 10 , R 11 The preferred solution of the present invention is more conducive to improving the stability of quantum dots, while ensuring excellent optical properties and further effectively avoiding the appearance of black and yellow dots.

[0098] In the present invention, there is no restriction on the form of the boron-containing quantum dot complex aggregates, which can be selected according to practical applications.

[0099] In some preferred embodiments of the present invention, the boron-containing quantum dot complex aggregate is a boron-containing quantum dot dispersion, and the boron content in the boron-containing quantum dot dispersion is 1000ppm-9000ppm, for example, specifically 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm, 6000ppm, 6500ppm, 7000ppm, 7500ppm, 8000ppm, 8500ppm, 9000ppm, etc. and the range between any two values. With this preferred suitable boron content, the stability of the boron-containing quantum dot dispersion is better, and the boron-containing compound has a stronger protective effect on the optical properties of the quantum dots.

[0100] In some preferred embodiments of the present invention, the boron-containing quantum dot composite aggregate is a boron-containing quantum dot composite plate, and the content of boron in the boron-containing quantum dot composite plate is 13ppm-1750ppm, for example, specifically 13ppm, 20ppm, 30ppm, 40ppm, 50ppm, 60ppm, 70ppm, 80ppm, 90ppm, 100ppm, 200ppm, 300ppm, 400ppm, 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1100ppm, 1200ppm, 1300ppm, 1400ppm, 1500ppm, 1600ppm, 1700ppm, 1750ppm, etc. and the range between any two values. With this preferred suitable boron content, the stability of the boron-containing quantum dot composite plate is gradually better, and the protective effect of the boron-containing compound on the optical properties of the quantum dots is stronger.

[0101] The boron-containing quantum dot composite plate of the present invention can be further prepared by conventionally using the corresponding quantum dot dispersion as a raw material, or can be directly prepared by using the corresponding boron-containing compound as a raw material. In the present invention, compared with the boron-containing quantum dot composite plate, the boron-containing quantum dot dispersion has a higher content of quantum dots, so that the boron content can be at a higher level to facilitate processing and handling efficiency.

[0102] In the present invention, the tri-coordinated boron-containing compound is covalently bonded to the anions on the surface of the quantum dots (such as sulfur, selenium, oxygen, nitrogen, phosphorus and other V, VI group elements) to form a tri-coordinated boron-containing quantum dot complex. Here, the surface of the quantum dots is ZnS, and the bonding process is as follows:

[0103] .

[0104] Compared with the traditional Z-type ligand, the anions adjacent to boron in the tri-coordinate boron quantum dot complex of the present invention have a stronger antioxidant capacity, which is due to: the empty P orbital of the tri-coordinate boron produces a conjugated effect with the lone pair of electrons of the adjacent anion. Affected by the conjugated effect, the electrons of the anion are more difficult to be taken away by the oxidant. The tri-coordinate boron quantum dot complex directly combines the lone pair of electrons (such as sulfur) of the anion on the surface of the quantum dot through a coordination bond to form a tetra-coordinate boron quantum dot complex, and the reducing ability of the anion is significantly reduced, making it more difficult to be oxidized (the electrons of the anion affected by the coordination bond are more difficult to be taken away by the oxidant, and this effect is stronger than the conjugated effect).

[0105] In some preferred embodiments of the present invention, the tri-coordinate boron-containing quantum dot complex is selected from:

[0106] , , , , , , , , At least one of .

[0107] The tetracoordinated boron-containing quantum dot complex is selected from:

[0108] , , , , , , , , At least one of .

[0109] In some preferred embodiments of the present invention, the quantum dots are of a bare core structure, and the surface of the bare core structure has at least one of Group IVA atoms, Group VA anions, and Group VIA anions.

[0110] In some other preferred embodiments of the present invention, the quantum dots are of a core-shell structure, and the shell surface of the core-shell structure contains at least one of Group IVA atoms, Group VA anions, and Group VIA anions.

[0111] As long as the quantum dots in the prior art have at least one of Group IVA atoms, Group VA anions, and Group VIA anions on their surfaces, they can be used in the present invention, and can be chemically bonded with boron-containing compounds to form boron-containing quantum dot complex aggregates including tri-coordinate boron-containing quantum dot complexes and tetra-coordinate boron-containing quantum dot complexes.

[0112] The VA group anions and VIA group anions on the surface of the quantum dots may be, for example, anions corresponding to the VA group and VIA group elements such as sulfur, selenium, oxygen, nitrogen, and phosphorus.

[0113] In some specific embodiments of the present invention, the bare core structure quantum dots can be binary quantum dots (such as CdSe, CdS, ZnSe, ZnS quantum dots), M-element alloy quantum dots (M is a positive integer ≥ 3, ternary, quaternary, quinary and even higher elements are alloy quantum dots, which are obtained by mixing and alloying multiple binary components), etc. Exemplarily, the bare core structure quantum dots can be selected from IA-IVA-VIIA group compound semiconductors (such as CsPdCl3), IIIA-VA group compound semiconductors (such as InP), IVA-VIA group compound semiconductors (such as PdS), IVA-VIA-VIA group compound semiconductors (such as PdSeS), IIA-IIIA-VA group compound semiconductors, IIIA-VA-VIA group compound semiconductors (such as InPS), IIA-IIIA-VA group compound semiconductors, IIA-VIA group compound semiconductors, and IIA-VIA-VIA group compound semiconductors. A-VIA group compound semiconductors, IA-IIIA-IVA-VIA-VIIA group compound semiconductors, IB-IIIA-VIA group compound semiconductors (such as CuInS), IB-IIIA-VIA-VIA group compound semiconductors (such as CuInSeS), IIB-VIA group compound semiconductors (such as CdSe), IIIA-IIB-VA group compound semiconductors (such as InZnP), IIB-IIIA-VIA group compound semiconductors, IIB-IIIA-VA-VIA group compound semiconductors, IB-IIIA-VIA group compound semiconductors, IB-IIB-IIIA-VIA group compound semiconductors, IIBIIB-VIA group compound semiconductors (such as ZnCdSe), IIBIIB-VIAVIA group compound semiconductors (such as ZnCdSeS), IIB-VIAVIA group compound semiconductors (such as CdSeS), IB-IIB-IVA-VIA group compound semiconductors, perovskite quantum dots, carbon quantum dots.

[0114] In some specific embodiments of the present invention, the feasible range of the core material of the core-shell structured quantum dots is consistent with the feasible range of the bare core structured quantum dots, and the shell material can be selected from inorganic compounds (such as inorganic oxides, sulfides, nitrides), organic polymer compounds (such as polyamides, polystyrene, etc.), silicone polymers (such as polytetramethoxysilane, polyphenyltrimethoxysilane), etc.

[0115] Furthermore, the shell material of the core-shell structured quantum dots can also include IIB-VIA compounds (such as ZnS, ZnO, etc.), IIA-VIA compounds (such as MgO), IIIA-VA compounds (such as BN), IIIA-VIA compounds (such as Al2O3, B2O3, etc.), IIIA-VIA compounds (such as Al2O3, B2O3, etc.), IVA-VIA compounds (such as SiO2), IVB-VIA compounds (such as ZrO2) and VIIA halide metal salt compounds (such as ZnCl2).

[0116] In the above-mentioned corresponding group compound semiconductors, elements of different groups can be arbitrarily combined, and one or more elements of the same group can be arbitrarily combined; for example, the IIB-VIA group compound semiconductor can be a combination of one or more elements in the IIB group and one or more elements in the VIA group, and the combination can be a bare core structure or a core-shell structure.

[0117] Exemplarily, quantum dots corresponding to IIB-VIA group compound semiconductors may include binary core-shell (such as CdSe / CdS, CdSe / ZnS, CdSe / CdS / ZnS, CdTe / ZnS, CdS / ZnS, etc.), ternary core-shell (such as CdSeS / ZnS, ZnCdSe / ZnS, CdSeTe / ZnS, etc.), quaternary core-shell (such as ZnCdSeS / ZnS, ZnCdSeTe / ZnS, etc.). It can be understood that CdSe / CdS refers to a core-shell structure with CdSe as the core and CdS as the shell, and ZnCdSe / ZnS refers to a core-shell structure with ZnCdSe as the core and ZnS as the shell, and the same is true for the others.

[0118] Exemplarily, quantum dots corresponding to Group IIB-IIIA-VIA compound semiconductors may include, for example, CuInSe2, CuInS2, CuInSe2 / ZnS, and CuInS2 / ZnS.

[0119] Exemplarily, the quantum dots corresponding to the IVA-VIA group compound semiconductors may include: SnS, SnSe, SnTe, PbS, PbSe, PbTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbSSe, SnPbSeTe, SnPbSTe, etc.

[0120] Exemplarily, quantum dots corresponding to Group IB-IIB-IVA-VIA compound semiconductors may include, for example, CuZnSnSe, CuZnSnS, and the like.

[0121] Exemplarily, quantum dots corresponding to IIIA-VA group compound semiconductors may include, for example, GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, InP / ZnS, InP / ZnSe / ZnS, etc.

[0122] The boron-containing quantum dot complex aggregates of the present invention may exist in any form, for example, in the form of a solution or in the form of a plate.

[0123] In the present invention, the structures of the tri-coordinate boron-containing quantum dot complex and the tetra-coordinate boron-containing quantum dot complex in the boron-containing quantum dot complex aggregate can be determined by nuclear magnetic resonance. 11 The absorption spectra are tested by B spectrum, synchrotron radiation absorption test, covalent bond infrared characteristic absorption spectrum and other absorption spectra. These testing methods are all existing technologies and will not be described in detail here.

[0124] In a second aspect, the present invention provides a method for preparing a boron-containing quantum dot dispersion, comprising the following steps:

[0125] S1. Prepare a boron-containing compound and a dispersing solvent;

[0126] S2, adding quantum dots into a system of boron-containing compounds and a dispersing solvent and introducing an inert gas;

[0127] S3, heating, mixing and dispersing the system obtained in S2, and keeping the temperature for reaction; during the reaction, the boron-containing compound reacts with the quantum dots to form a tri-coordinate boron-containing quantum dot complex and a tetra-coordinate boron-containing quantum dot complex, the boron-containing compound in the tri-coordinate boron-containing quantum dot complex is covalently bonded to the quantum dots, and the boron-containing compound in the tetra-coordinate boron-containing quantum dot complex is coordination-bonded to the quantum dots, the ratio of XB coordination bonds in the boron-containing quantum dot dispersion to the sum of the number of XB covalent bonds and XB coordination bonds is 0.10%-50%, and X is selected from X1, X2, X3, X4, X5, and X6;

[0128] S4, cooling;

[0129] In S3, the chemical formula of the tri-coordinate boron-containing quantum dot complex is as shown in the following formula 1, and the chemical formula of the tetra-coordinate boron-containing quantum dot complex is as shown in the following formula 2;

[0130] Formula 1; Formula 2;

[0131] Wherein, QD is quantum dot; R8, R9, R 10 , R 11 , R 12 , R 13Each of them is independently selected from alkoxy, hydrocarbon, substituted hydrocarbon, halogen, carboxyl, hydroxyl, aldehyde, ester and amide, the substituent in the substituted hydrocarbon is selected from at least one of halogen, hydroxyl, alkoxy, carboxyl, aldehyde, ester and amide, n1=natural number, n2=natural number, X1, X2, X3, X4, X5 and X6 are each independently selected from VIA group elements, VA group elements and IVA group elements.

[0132] Preferably, the content of boron element in the boron-containing quantum dot dispersion is 1000ppm-9000ppm.

[0133] In some preferred embodiments of the second aspect of the present invention, in S2, the mass ratio of quantum dots to boron-containing compounds is 1:0.25-5. This preferred embodiment can enhance the direct covalent bonding between quantum dots and boron-containing compounds, thereby further improving the proportion of tri-coordinate boron-containing quantum dot complexes.

[0134] In some preferred embodiments of the second aspect of the present invention, the mass ratio of the boron-containing compound to the dispersing solvent in S1 is 0.01-0.5: 1. This preferred solution can promote the dispersion of the boron-containing compound while enhancing the coupling effect between the boron-containing compounds (the natural numbers of n1 and n2 are larger), thereby being more conducive to improving the structural stability of the tri-coordinate and tetra-coordinate boron-containing quantum dot complexes (better than more and stronger binding sites between BX).

[0135] In some preferred embodiments of the second aspect of the present invention, the dispersing solvent in S1 includes at least one of alkanes, aromatic hydrocarbons, organic amines, octadecene, organic carboxylic acids containing 1 to 18 carbon atoms, liquid paraffin, acrylates, organic silanes, and organic phosphines. The organic carboxylic acids containing 1 to 18 carbon atoms can be selected from, for example, caprylic acid, oleic acid, linoleic acid, stearic acid, and the like.

[0136] In some preferred embodiments of the second aspect of the present invention, the reaction temperature of the heat preservation reaction in S3 is higher than the melting point of the boron-containing compound and the dispersion solvent, and lower than the boiling point of the boron-containing compound and the dispersion solvent, and the reaction time is 0.1h-3h. By adopting this preferred embodiment, the solvent can be made liquid while avoiding the volatilization of the solvent due to excessively high reaction temperature, thereby being more conducive to improving the degree of reaction.

[0137] Preferably, the stirring speed of the mixing and dispersing is 100 rpm-300 rpm. This preferred solution can avoid the material from splashing and hanging on the wall, thereby being more conducive to improving the uniformity of the reaction.

[0138] The reaction temperature of the insulation reaction in S3 of the present invention can be determined according to the ratio of covalent bonds and coordination bonds to be formed. For example, it can be a high temperature range of 100°C-300°C, preferably 100°C-230°C, which is conducive to the formation of covalent bonds, or a low temperature range of 30°C-100°C, which is conducive to the formation of coordination bonds and is not equal to 100°C.

[0139] In some preferred embodiments of the second aspect of the present invention, when the ratio of covalent bonds needs to be increased, the reaction temperature in S3 is controlled to be 100° C.-300° C., preferably 100° C.-230° C.; when the ratio of coordination bonds needs to be increased, the reaction temperature in S3 is controlled to be 30° C.-100° C. and not equal to 100° C. This preferred solution can more quickly and accurately regulate the ratio of covalent bonds and coordination bonds.

[0140] In some preferred embodiments of the second aspect of the present invention, the quantum dots are core-shell structures or bare core structures, and the quantum dots are present in the form of solids or concentrated solutions, and the mass fraction of the quantum dots in the concentrated solution is 5%-50%. By adopting this preferred embodiment, the concentration of the reactants (quantum dots) can be increased as much as possible while ensuring that the system solution is homogeneous, thereby further improving the processing efficiency of the boron-containing quantum dot dispersion.

[0141] In the solution where the quantum dots are present in the form of a concentrated solution, the solvent in the concentrated solution may be, for example, at least one of alkanes (such as hexane, octane, liquid paraffin, octadecene, etc.), aromatic hydrocarbons (such as toluene), organic amines (such as trioctylamine), organic carboxylic acids containing 1 to 18 carbon atoms (such as oleic acid), organic lipids (such as acrylates), organic silanes (such as mercaptopropyltrimethoxysilane), and organic phosphines (such as trioctylphosphine). Those skilled in the art may select the solvent in the concentrated solution according to actual needs.

[0142] In some preferred embodiments of the second aspect of the present invention, the boron-containing compound comprises at least one of the corresponding compounds of the following three general formulae and their dehydration condensation, esterification, and amidation derivative compounds:

[0143] General formula 1, , R1, R2, and R3 are each independently selected from a hydrocarbon group, an alkoxy group, a halogen group, and a substituted hydrocarbon group;

[0144] General formula 2: , R4 and R5 are each independently selected from carboxyl, substituted hydrocarbon, halogen, hydrocarbon, alkoxy, and hydroxyl;

[0145] General formula three: , R6 is selected from H or selected from hydrocarbon group, substituted hydrocarbon group, halogen, aldehyde group, carboxyl group, and R7 is selected from hydrocarbon group, alkoxy group, hydroxyalkyl group, and hydroxyl group.

[0146] Further preferably, in the three general formulas, the substituents in the substituted hydrocarbon group are independently selected from at least one of halogen, hydroxyl, alkoxy, carboxyl, aldehyde, ester, and amide. The hydrocarbon group may be a straight-chain hydrocarbon group, a branched hydrocarbon group, or a cyclic hydrocarbon group. As long as the above ranges and the corresponding general structure and the corresponding coordinated boron-containing quantum dot complex mass content are met, the effects of the present invention can be achieved.

[0147] It is understandable that the boron-containing compound may conform to one of the three general formulas above, or may conform to multiple of the three general formulas above, for example, it may include at least one compound of general formula one, at least one compound of general formula two, and at least one compound of general formula three.

[0148] It is understood that the hydrocarbon group is selected from alkyl, aryl, alkenyl, and alkynyl.

[0149] In some preferred embodiments of the present invention, the boron-containing compound includes at least general formula three, which is more conducive to improving its dispersibility in a polymer substrate (such as polystyrene (PS)) while enhancing the electron-withdrawing effect of boron through the induction effect and improving its protection of anions.

[0150] In some preferred embodiments of the second aspect of the present invention, the number of carbon atoms in any carbon-containing group in Formula 1, Formula 2, and Formula 3 is less than 18.

[0151] Further preferably, in Formula 2, R4 is selected from carboxyl, substituted hydrocarbon, allyl, aryl, and hydroxyl, and R5 is selected from alkoxy, hydroxyl, hydroxyalkyl, and hydrocarbon.

[0152] Among them, R6 can be selected from one or more of the aforementioned ranges, and different groups of R6 can be distributed at different positions of the benzene ring in general formula 3. In some more preferred embodiments of the second aspect of the present invention, in general formula 3, the group position of R6 is meta-position m or para-position p, which is more conducive to the electron-withdrawing group to enhance the electron-capturing ability of the empty orbital of the boron atom, and further improve the antioxidant effect of the tetracoordinated boron quantum dot complex bound by coordination bonds.

[0153] In some embodiments of the present invention, the boron-containing compound is selected from the following compounds:

[0154] , , , , , wait.

[0155] In the second aspect, the use of a preferred range of boron-containing compounds is more conducive to the dissolution and dispersion of the boron-containing compounds in a high-concentration quantum dot solution and increases the covalent binding ability with the surface of the quantum dots.

[0156] In the preparation method of the second aspect of the present invention, the ratio of coordination bonds and covalent bonds can be controlled by adjusting the time, temperature and other conditions of the thermal insulation reaction of the boron-containing compound.

[0157] In a third aspect, the present invention provides a boron-containing quantum dot dispersion liquid, which is prepared by the preparation method of the boron-containing quantum dot dispersion liquid described in the second aspect.

[0158] In a fourth aspect, the present invention provides a method for preparing a boron-containing quantum dot composite plate, comprising the following steps:

[0159] S101, provide boron-containing compounds, quantum dot concentrates, polymer granules, and sheet functional additives;

[0160] S102, mixing the quantum dot concentrate with at least part of the polymer pellets to obtain a quantum dot polymer mixture;

[0161] S103, melt-extrude the quantum dot polymer mixture, the boron-containing compound, and the plate functional additive to form a boron-containing quantum dot composite plate; during the process, the boron-containing compound reacts with the quantum dots to form a tri-coordinate boron-containing quantum dot composite and a tetra-coordinate boron-containing quantum dot composite, the boron-containing compound in the tri-coordinate boron-containing quantum dot composite is covalently bonded to the quantum dots, and the boron-containing compound in the tetra-coordinate boron-containing quantum dot composite is coordination-bonded to the quantum dots, and the ratio of XB coordination bonds to the sum of the number of XB covalent bonds and XB coordination bonds in the boron-containing quantum dot composite plate is 0.10%-50%, and X is selected from X1, X2, X3, X4, X5, and X6;

[0162] In S103, the chemical formula of the tri-coordinate boron-containing quantum dot complex is as shown in the following formula 1, and the chemical formula of the tetra-coordinate boron-containing quantum dot complex is as shown in the following formula 2;

[0163] Formula 1; Formula 2;

[0164] Wherein, QD is quantum dot; R8, R9, R 10 , R 11 , R 12 , R 13 Each of them is independently selected from alkoxy, hydrocarbon, substituted hydrocarbon, halogen, carboxyl, hydroxyl, aldehyde, ester and amide, the substituent in the substituted hydrocarbon is selected from at least one of halogen, hydroxyl, alkoxy, carboxyl, aldehyde, ester and amide, n1=natural number, n2=natural number, X1, X2, X3, X4, X5 and X6 are each independently selected from VIA group elements, VA group elements and IVA group elements.

[0165] Preferably, the content of boron element in the boron quantum dot composite plate is 13ppm-1750ppm.

[0166] In some preferred embodiments of the fourth aspect of the present invention, the mass ratio of the quantum dots to the total amount of the boron-containing compound is 1:0.5-40.

[0167] Further preferably, the mass of the boron-containing compound used for coordination and bonding with other lone pairs of electrons or conjugated electron donors other than quantum dots in the raw materials in the total amount of the boron-containing compound is 1.2%-1000% of the mass of the quantum dots. With this preferred solution, it is possible to combine with Lewis bases (electron donors) other than quantum dots while protecting the anions on the surface of the quantum dots, thereby being more conducive to improving the thermal conductivity and antioxidant capacity of the plate through the boron-containing complex.

[0168] Among them, it is used to react with other lone pair electrons or conjugated electron donors in the raw materials other than quantum dots, such as antioxidants, light stabilizers, Group V and VI elements on hindered amines, as well as benzene rings, olefins, alkynes, etc.

[0169] In some preferred embodiments of the fourth aspect of the present invention, the conditions of the melt extrusion in S103 include: a processing temperature of 210° C.-270° C., and a reaction time of 1-2 min.

[0170] In some preferred embodiments of the fourth aspect of the present invention, the stirring speed of the first mixing in S102 is 300-700 rpm.

[0171] The boron-containing quantum dot composite plate of the present invention can be used in a variety of quantum dot application fields, and the corresponding plate functional additives and polymer granules can be selected according to different application fields. In some preferred embodiments of the fourth aspect of the present invention, the boron-containing quantum dot composite plate is a boron-containing quantum dot optical diffusion plate, and the corresponding plate functional additives include at least one of an antioxidant, a light diffuser, a toughening agent, and a light stabilizer. Among them, the raw materials other than the boron-containing compound and the quantum dots are common additives in traditional ordinary diffusion plates. In order to ensure the balanced performance of the processed products, the amount of each common additive can be referred to the corresponding range in the prior art.

[0172] Further preferably, the melt extrusion process of S103 includes: performing a second mixed extrusion of the boron-containing compound, the antioxidant, the light stabilizer, and another part of the polymer pellets to obtain the auxiliary agent pellets; then feeding the quantum dot polymer mixture and the auxiliary agent pellets into the first extruder, and feeding the diffusant and the toughening agent into the second extruder and the third extruder respectively, and then performing melt extrusion. Further preferably, the temperature of the second mixed extrusion is 180°C-220°C.

[0173] Further preferably, in S101, based on the total amount of raw materials, the mass fraction of the boron-containing compound is 0.05%-1%, the mass fraction of the quantum dot concentrate is 0.05%-0.2%, the mass fraction of quantum dots in the quantum dot concentrate is 5%-50%, the mass fraction of the antioxidant is 0.1%-2%, the total mass fraction of the light diffuser and the toughening agent is 0.5%-2%, and the mass fraction of the light stabilizer is 0.05%-2%. The adoption of this preferred solution is more conducive to the balanced performance of the quantum dot diffusion plate produced, meeting the requirements of production line processing and product life.

[0174] Preferably, the quantum dots include red quantum dots and / or green quantum dots.

[0175] Preferably, the polymer particles are selected from polystyrene, polymethyl methacrylate, polycarbonate, polyethylene, and polypropylene.

[0176] Preferably, the thickness of the boron quantum dot composite plate is 1.2 mm to 3.0 mm. A suitably thin boron quantum dot composite plate is more conducive to providing a certain mechanical strength and optical path while reducing the amount of substrate in the plate and reducing the cost of raw materials.

[0177] The optional range of the boron-containing compound in the fourth aspect of the present invention is the same as that of the boron-containing compound in the second aspect, and will not be described in detail here.

[0178] The selection of the boron-containing compound in the methods of the second aspect and the fourth aspect of the present invention can be selected based on whether it is conducive to chemical bonding. Preferably, in the preparation of the dispersion of the second aspect of the present invention, since the mass fraction of quantum dots is relatively high (such as 10%), the structure of the selected boron-containing compound only needs to have a high solubility in the system to match the high concentration of quantum dots and facilitate chemical bonding; further preferred are boron-containing compounds with hydroxyl groups and / or alkoxy groups, which can further form a more solid tri-coordinate structure with the surface of quantum dots by utilizing the hydrolysis of alkoxy groups and the binding ability of hydroxyl groups.

[0179] In the preparation of the composite board of the fourth aspect of the present invention, the mass fraction of quantum dots is low (such as 0.1%), and the range of composite board substrates such as PS, PMMA, PC, etc. is relatively fixed, so the boron-containing compound should be more in line with the chemical environment of the diffusion plate. For example, in the polystyrene substrate, boron-containing compounds containing alkyl or aryl groups are preferred, which is conducive to chemical bonding. Boron-containing compounds with alkyl and / or aryl groups are further preferred, which can utilize the hydrophobicity of alkyl and / or aryl groups to improve the dispersibility in the PS substrate and form a more oxidation-resistant four-coordinate structure with the surface of quantum dots.

[0180] In the preparation of the composite board of the fourth aspect of the present invention, the ratio of coordination bonds and covalent bonds can be controlled by adjusting the temperature of the second mixed extrusion, the extrusion temperature of the melt extrusion, the extrusion speed, the extrusion time and other conditions.

[0181] In a fifth aspect, the present invention provides a boron-containing quantum dot composite plate, which is prepared by the preparation method of the boron-containing quantum dot composite plate described in the fourth aspect.

[0182] Compared with the conventional method of directly using quantum dot concentrate to prepare quantum dot PS optical sheets, the present invention adopts a method of directly preparing boron quantum dot composite boards using boron-containing compounds, and the obtained boron quantum dot composite boards have better stability and product aging performance.

[0183] In a sixth aspect, the present invention provides an application of the boron-containing quantum dot complex aggregate described in the first aspect in a quantum dot diffusion plate, a quantum dot light-converting agricultural film, a quantum dot on-chip package, and a quantum dot electroluminescent device.

[0184] The embodiments of the present invention are described in detail below, which are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0185] 1. Preparation of boron-containing quantum dot dispersion:

[0186] Example 1

[0187] 200 g of decane, 10 g of dodecylboric acid, 2 g of 4-methylphenylboric acid, and 2 g of oleic acid were placed in a 500 mL four-necked stirred reactor with a condensing reflux device, argon was introduced and stirring was started (speed 100 rpm), and 20 g of CdSe / CdS / ZnS core-shell red quantum dot solid (Em (i.e., emission wavelength) = 625 nm, Fwhm (i.e., half maximum full width) = 23 nm) was added to the system. After the quantum dot solid was dispersed, the system was heated to 160°C (i.e., reaction temperature), kept warm for 2 h, and then cooled to 30°C to obtain a uniform boron-containing quantum dot dispersion.

[0188] Example 2

[0189] 200 g of tri-n-octylamine, 10 g of boric acid, and 20 g of oleic acid were placed in a 500 mL four-necked stirred reactor with a condensing reflux device, argon was introduced and stirring was started (speed 200 rpm), 20 g of CdSe / CdS / ZnS core-shell red quantum dot solid (Em=625 nm, Fwhm=23 nm) was added to the system, and after the quantum dot solid was dispersed, the system was heated to 220 °C, kept warm for 2 h, and then cooled to 30 °C to obtain a uniform boron-containing quantum dot dispersion.

[0190] Example 3

[0191] 200 g of octane, 10 g of trioctyl borate, 1 g of boric acid, and 2 g of oleic acid were placed in a 500 mL four-necked stirred reactor with a condensing reflux device, argon was introduced and stirring was started (speed 100 rpm), 20 g of CdSe / CdS / ZnS core-shell green quantum dot solid (Em=538 nm, Fwhm=23 nm) was added to the system, and after the quantum dot solid was dispersed, the system was heated to 100 °C, kept warm for 2 h, and then cooled to 30 °C to obtain a uniform boron-containing quantum dot dispersion.

[0192] Among them, an appropriate amount of oleic acid can increase the polarity of the mixed solvent formed by octane and oleic acid, and promote dissolution; at the same time, it plays the role of a surface ligand for dispersing solid quantum dots to a certain extent.

[0193] Example 4

[0194] 200 g of liquid paraffin, 10 g of difluorophenylboric acid, 2 g of trioctyl borate, and 2 g of oleic acid were placed in a 500 mL four-necked stirred reactor with a condensing reflux device, argon was introduced and stirring was started (speed 100 rpm), and 20 g of CdSe / CdS / ZnS core-shell green quantum dot solid (Em=538 nm, Fwhm=23 nm) was added to the system. After the quantum dot solid was dispersed, the system was heated to 230°C, kept warm for 2 hours, and then cooled to 30°C to obtain a uniform boron-containing quantum dot dispersion.

[0195] Example 5

[0196] 100 g of trimethoxyphenylsilane, 100 g of trimethoxydodecylsilane, 10 g of hydroxymethylphenylboric acid, and 2 g of oleic acid were placed in a 500 mL four-necked stirred reactor with a condensing reflux device, argon was introduced and stirring was started (speed 100 rpm), 20 g of CdSe / CdS / ZnS core-shell green quantum dot solid (Em=538 nm, Fwhm=23 nm) was added to the system, and after the quantum dot solid was dispersed, the system was heated to 180 °C, kept warm for 1 h, and then cooled to 30 °C to obtain a uniform boron-containing quantum dot dispersion.

[0197] Example 6

[0198] 200 g of trioctylphosphine, 10 g of trioctyl borate, and 2 g of boric acid were placed in a 500 mL four-necked stirred reactor with a condensing reflux device, argon was introduced and stirring was started (speed 100 rpm), 20 g of CdSe / CdS / ZnS core-shell green quantum dot solid (Em=538 nm, Fwhm=23 nm) was added to the system, and after the quantum dot solid was dispersed, the system was heated to 200 °C, kept warm for 2 h, and then cooled to 30 °C to obtain a uniform boron-containing quantum dot dispersion.

[0199] Example 7

[0200] 200 g of octane, 10 g of boric acid, and 2 g of diisooctylphosphinic acid were placed in a 500 mL four-necked stirred reactor with a condensing reflux device, argon was introduced and stirring was started (speed 100 rpm), 20 g of CdSe / CdS / ZnS core-shell red quantum dot solid (Em=625 nm, Fwhm=23 nm) was added to the system, and after the quantum dot solid was dispersed, the system was heated to 110°C, kept for reaction for 2 h, and then cooled to 30°C to obtain a uniform boron-containing quantum dot dispersion.

[0201] Example 8

[0202] 200 g of toluene, 10 g of tributyl boron and 2 g of 4-methylphenylboric acid were placed in a 500 mL four-necked stirred reactor with a condensing reflux device, argon was introduced and stirring was started (speed 100 rpm), 20 g of CdSe / CdS / ZnS core-shell green quantum dot solid (Em=538 nm, Fwhm=23 nm) was added to the system, and after the quantum dot solid was dispersed, the system was heated to 200 °C, kept warm for 2 h, and then cooled to 30 °C to obtain a uniform boron-containing quantum dot dispersion.

[0203] Example 9

[0204] 200 g of isobornyl methacrylate, 10 g of dimethoxyphenylboric acid, and 2 g of oleic acid were placed in a 500 mL four-necked stirred reactor with a condensing reflux device, argon was introduced and stirring was started (speed 100 rpm), and 20 g of CdSe / CdS / ZnS core-shell red quantum dot solid (Em=625 nm, Fwhm=23 nm) was added to the system. After the quantum dot solid was dispersed, the system was heated to 180°C, kept warm for 2 hours, and then cooled to 30°C to obtain a uniform boron-containing quantum dot dispersion.

[0205] Example 1-a

[0206] The method is carried out in accordance with Example 1, except that the reaction temperature after the quantum dots are solid dispersed is increased until the ratio of BX covalent bonds to BX coordination bonds reaches the ratio described in Table 2, and the reaction temperature is below 300°C.

[0207] Example 1-b

[0208] The method is carried out in accordance with Example 1, except that the reaction temperature after the quantum dots are solid dispersed is lowered until the ratio of BX covalent bonds to BX coordination bonds reaches the ratio described in Table 2, and the reaction temperature is 30°C-100°C and less than 100°C.

[0209] Example 1-c

[0210] The process is carried out with reference to Example 1, except that the type of quantum dots is different, specifically replaced with core-shell structure CdZnSe / ZnSe / ZnS quantum dots, and the amount used remains unchanged.

[0211] Example 1-d

[0212] The process is carried out with reference to Example 1, except that the type of quantum dots is different, specifically, quaternary ZnCdSeS alloy quantum dots with a bare core structure are used instead, and the amount used remains unchanged.

[0213] Example 1-e

[0214] The process was carried out with reference to Example 1, except that the types of boron-containing compounds were different, specifically 10 g of boron tribromide and 2 g of 4-methylphenylboric acid.

[0215] Example 1-f

[0216] The method was carried out with reference to Example 1, except that the types of boron-containing compounds were different, specifically 10 g of hydroxyborane dibromide (prepared by slowly adding 1 equivalent of water to 3 equivalents of boron tribromide and partially hydrolyzing it, and the preparation was immediate and the subsequent preparation was the same), and 2 g of 4-methylphenylboronic acid.

[0217] Example 1-g

[0218] The process was carried out with reference to Example 1, except that the types of boron-containing compounds were different, specifically 10 g of 3-carboxypropylboric acid and 2 g of 4-methylphenylboric acid.

[0219] Example 1-h

[0220] The process was carried out with reference to Example 1, except that the types of boron-containing compounds were different, specifically 10 g of 4-bromobutylboric acid and 2 g of 4-methylphenylboric acid.

[0221] Example 1-i

[0222] The method was carried out with reference to Example 1, except that the types of boron-containing compounds were different, specifically 10 g of monoethyl phenylborate (obtained by controlled hydrolysis of diethyl phenylborate, prepared and used immediately, and the subsequent configuration was the same), and 2 g of 4-methylphenylboric acid.

[0223] Example 1-j

[0224] The process was carried out with reference to Example 1, except that the types of boron-containing compounds were different, specifically 10 g of diphenylboric acid and 2 g of 4-methylphenylboric acid.

[0225] Example 1-k

[0226] The process is carried out with reference to Example 1, except that the types of boron-containing compounds are different, specifically 10 g of 4-trifluoromethylphenylboric acid and 2 g of 4-methylphenylboric acid.

[0227] Embodiment 1-1

[0228] The process was carried out with reference to Example 1, except that the types of the boron-containing compounds were different, specifically 10 g of 3-formylphenylboronic acid and 2 g of 4-methylphenylboronic acid.

[0229] Example 1-m

[0230] The process was carried out with reference to Example 1, except that the types of boron-containing compounds were different, specifically 10 g of 4-carboxyphenylboric acid and 2 g of 4-methylphenylboric acid.

[0231] Comparative Example 1

[0232] CdSe / CdS / ZnS core-shell green quantum dots octane dispersion (Em=538 nm, Fwhm=23 nm). The mass fraction of quantum dots in the green quantum dots octane dispersion is ≈17%.

[0233] Comparative Example 2

[0234] CdSe / CdS / ZnS green core-shell quantum dot dispersion after treatment with organothiol metal salt (Em=538 nm, Fwhm=23 nm). The mass ratio of organothiol metal salt to green core-shell quantum dots is 0.6:1.

[0235] Comparative Example 3

[0236] CdSe / CdS / ZnS green core-shell quantum dot dispersion after treatment with metal organophosphonate (Em=538 nm, Fwhm=23 nm). The mass ratio of metal organophosphonate to green core-shell quantum dots is 0.6:1.

[0237] Comparative Example 4

[0238] CdSe / CdS / ZnS core-shell red quantum dots octane dispersion (Em=625 nm, Fwhm=23 nm). The mass fraction of quantum dots in the red quantum dots octane dispersion is ≈17%.

[0239] Comparative Example 5

[0240] Octane dispersion of CdSe / CdS / ZnS core-shell red quantum dots after treatment with organic thiol metal salt (Em=625 nm, Fwhm=23 nm); the mass ratio of organic thiol metal salt to red core-shell quantum dots is 0.6:1.

[0241] Comparative Example 6

[0242] CdSe / CdS / ZnS red core-shell quantum dots dispersion after treatment with organophosphonic acid metal salt (Em=625 nm, Fwhm=23 nm). The mass ratio of organophosphonic acid metal salt to red core-shell quantum dots is 0.6:1.

[0243] Comparative Example 9

[0244] The method is carried out in accordance with Example 1, except that the proportion of BX covalent bonds and BX coordination bonds is controlled to reach the proportion described in Table 2. In order to meet the change in conditions, the following adjustments are required: the amount of boron-containing compounds (dodecylboric acid and 4-methylphenylboric acid) added is reduced by 90%, respectively, while the other conditions remain unchanged.

[0245] Comparative Example 10

[0246] The method is carried out in accordance with Example 1, except that the proportion of BX covalent bonds and BX coordination bonds is controlled to reach the proportion described in Table 2. To meet the change in the condition, the amount of quantum dots added is increased by 10 times, and the other conditions remain unchanged.

[0247] Test Example 1

[0248] 1. The corresponding quantum dot dispersions (such as boron-containing quantum dot dispersions or boron-free quantum dot dispersions) obtained in the above embodiments and comparative examples were respectively measured for B element content using ICP-OES (inductively coupled plasma optical emission spectrometer). The results are shown in Tables 1 and 2.

[0249] and by molecular absorption spectroscopy (NMR 11 B spectrum) detects the ratio of BX covalent bonds and BX coordination bonds in the corresponding quantum dot dispersion of each example, and the results are shown in Tables 1 and 2.

[0250] 2. The corresponding quantum dot dispersions obtained in the above examples and comparative examples were used to prepare conventional quantum dot PS (polystyrene) optical sheets, and then aged, and the changes in PLQY (i.e., photoluminescence quantum yield) of the sheets were tracked.

[0251] The preparation method of quantum dot PS optical sheet is as follows:

[0252] Take a certain mass of PS pellets, additives (generally hindered phenol and hindered amine antioxidants, mainly to prevent oxidation and degradation during the PS melt extrusion process and in the harsh use environment in the later stage, here antioxidant 1010 and antioxidant 770 are compounded at a mass ratio of 2:1), and the corresponding quantum dot dispersion are placed in a mixer and mixed evenly. The mass ratio of PS pellets, additives, and corresponding quantum dot dispersion is 825:8.33:1. Use a feeding funnel to add the above mixed pellets to a micro twin-screw extruder, melt shear and mix evenly, and then extrude the sample strip (extrusion processing temperature 260℃), and use a tablet press to form a sheet of 10cm×10cm×1mm. The mass fraction of the quantum dot dispersion is 0.12%, the mass fraction of the additive is 1%, and the mass fraction of PS is the remainder.

[0253] The above quantum dot PS optical sheet was subjected to an aging test under the conditions of 85°C, 90% RH, 800 W / m 2 Blue light irradiance (blue light wavelength is 450 nm), under this condition, 1mm thick quantum dot PS optical sheet will warp, and a fixing clamp is needed to fix the edge of the sheet in the aging box. The aging process test time is generally 24-72h (the specific time is subject to the actual test time). The quantum yield (PLQY) of the quantum dot PS optical sheet is measured using an integrating sphere. The results are shown in Table 1, Table 2, Figure 1 , Figure 2 In Table 1 and Table 2, “ / ” indicates that the quantum yield decreases too much (i.e., the decrease in green is greater than 20%, and the decrease in red is greater than 15%), and the test is stopped. In Table 1 and Table 2, “D” indicates a comparative example, and “S” indicates an example.

[0254] The density of black and yellow spots on the board surface was measured by a CCD appearance detector, where the definition of "black and yellow spots" is a local dark spot with a diameter greater than 0.1 mm that can be identified by the CCD appearance detector. The results are shown in Table 1-2. The density of black and yellow spots on the board surface in the subsequent tables is expressed as "β" (unit: pieces / m 2 ).

[0255] Table 1 Test results of green quantum dots corresponding examples

[0256]

[0257] Table 2 Test results of red quantum dots corresponding to examples

[0258]

[0259] Table 1, Table 2, Figure 1 , Figure 2The stability data show that: the embodiment of the present invention uses an appropriate amount of boron-containing compounds to treat and coat the surface of quantum dots to prepare boron-containing quantum dot composite aggregates, thereby protecting the anions on the surface of the quantum dots and having good heat resistance. The quantum dot material is used to prepare quantum dot PS sheets. In the absence of a water and oxygen barrier film, the stability of the quantum dots is significantly improved compared to the prior art, and can withstand high temperature and high humidity blue light aging for more than 1500 hours (85°C, 90%RH, 800 W / m 2 ), while effectively avoiding the appearance of black and yellow spots.

[0260] Further, using R8, R9, R 10 , R 11 do not contain phenyl at the same time; and / or, R8 and R9 are not halogen at the same time, and R 10 , R 11 The embodiments that are not halogens at the same time are more conducive to improving the stability of quantum dots, while ensuring excellent optical properties and further effectively avoiding the appearance of black and yellow spots.

[0261] 2. Preparation of Boron Quantum Dot Optical Diffuser Plate:

[0262] Example 10

[0263] Step (1) 200 kg of PS pellets, 500 g of green quantum dot concentrate (mass fraction ≈ 17%, solvent is n-octane), and 100 g of red quantum dot concentrate (mass fraction ≈ 17%, solvent is n-octane) are placed in a high-speed stirrer (stirring speed is 500 rpm) and stirred for 3 min to mix evenly to obtain a quantum dot polymer mixture for standby use.

[0264] Step (2) 0.5 kg of boric acid, 0.5 kg of dodecylboric acid, 1 kg of antioxidant 1076, 0.5 kg of light stabilizer 123, and 47.5 kg of PS pellets are mixed and stirred evenly, and then extruded and granulated to obtain auxiliary agent pellets. The extrusion temperature is 200° C. and the mixture is set aside.

[0265] Step (3) Using a loss-in-weight scale, add a uniformly mixed quantum dot polymer mixture and additive pellets to the B-layer extruder, add 25kg of PS diffusion masterbatch to the A-layer extruder, and add 25kg of PS toughening masterbatch to the C-layer extruder, and extrude together to form a three-layer structure plate of AC sandwiched with B. The quantum dot concentrate accounts for 0.1% and the quantum dot mass accounts for 0.017% in the relative ABC three-layer structure plate. The above materials are subjected to high-temperature melt extrusion and calendering to obtain a quantum dot diffusion plate with a thickness of 1.5 mm. The melt extrusion processing temperature is 260°C and the reaction time is 1.5 min.

[0266] Embodiment 11

[0267] The process is carried out in accordance with Example 10, except that step (2) is different. Step (2) is as follows: 1 kg of boric acid, 0.7 kg of hydroxymethylphenylboric acid, 1 kg of antioxidant 1010, 0.5 kg of light stabilizer 770, and 46.8 kg of PS pellets are mixed and stirred evenly, and then extruded and granulated to obtain auxiliary agent pellets, and the mixture is set aside.

[0268] Example 12

[0269] The process is carried out in accordance with Example 10, except that step (2) is different. Step (2) is as follows: 1.2 kg of triethyl borate, 1.2 kg of cyclopropylboric acid, 1.2 kg of antioxidant MD-1024, 0.5 kg of light stabilizer 944, and 45.9 kg of PS pellets are mixed and stirred evenly, and then extruded and granulated to obtain auxiliary agent pellets, and the mixture is set aside.

[0270] Embodiment 13

[0271] The process is carried out in accordance with Example 10, except that step (2) is different. Step (2) is as follows: 0.3 kg of boric acid, 0.3 kg of dodecylboric acid, 1 kg of antioxidant 1076, 0.5 kg of light stabilizer 123, and 47.9 kg of PS pellets are mixed and stirred evenly, and then extruded and granulated to obtain auxiliary agent pellets, which are set aside.

[0272] Embodiment 14

[0273] The process is carried out in accordance with Example 10, except that step (2) is different. Step (2) is as follows: 0.6 kg of boric acid, 0.6 kg of dodecylboric acid, 1 kg of antioxidant 1076, 0.5 kg of light stabilizer 123, and 47.3 kg of PS pellets are mixed and stirred evenly, and then extruded and granulated to obtain auxiliary agent pellets, which are set aside.

[0274] Embodiment 15

[0275] The process is carried out in accordance with Example 10, except that step (2) is different. Step (2) is as follows: 1.2 kg of boric acid, 1.2 kg of dodecylboric acid, 1 kg of antioxidant 1076, 0.5 kg of light stabilizer 123, and 46.1 kg of PS pellets are mixed and stirred evenly, and then extruded and granulated to obtain auxiliary agent pellets, which are set aside.

[0276] Example 16

[0277] The same method is carried out as in Example 10, except that step (2) is different. Step (2) is as follows: 2 kg of boric acid, 2 kg of dodecylboric acid, 1 kg of antioxidant 1076, 0.5 kg of light stabilizer 123, and 44.5 kg of PS pellets are mixed and stirred evenly, and then extruded and granulated to obtain auxiliary agent pellets, which are set aside.

[0278] Example 10-a

[0279] The method is carried out in accordance with Example 10, except that the melt extrusion processing temperature in step (3) is increased until the ratio of BX covalent bonds to BX coordination bonds reaches the ratio shown in Table 5. The chemical structures of the tri-coordinate boron-containing quantum dot complex and the tetra-coordinate boron-containing quantum dot complex contained in the product remain unchanged.

[0280] Example 10-b

[0281] The method is carried out in accordance with Example 10, except that the melt extrusion processing temperature in step (3) is lowered until the proportion of BX covalent bonds and BX coordination bonds is controlled to reach the proportion described in Table 5. The chemical structures of the tri-coordinate boron-containing quantum dot complex and the tetra-coordinate boron-containing quantum dot complex contained in the product remain unchanged.

[0282] Example 10-c

[0283] The method is carried out with reference to Example 10, except that the type of quantum dots is different, specifically replaced with core-shell structure CdZnSe / ZnSe / ZnS quantum dots, and the amount used remains unchanged. The chemical structures of the tri-coordinate boron-containing quantum dot complex and the tetra-coordinate boron-containing quantum dot complex contained in the product remain unchanged.

[0284] Example 10-d

[0285] The method is carried out in accordance with Example 10, except that the type of quantum dots is different, specifically replaced with quaternary ZnCdSeS alloy quantum dots of bare core structure, and the amount used remains unchanged. The chemical structures of the tri-coordinate boron-containing quantum dot complex and the tetra-coordinate boron-containing quantum dot complex contained in the product remain unchanged.

[0286] Example 10-e

[0287] The method is carried out with reference to Example 10, except that the amount of boric acid used in step (2) is adjusted to 0 kg and the amount of dodecylboric acid used is adjusted to 1 kg. In this embodiment, the mass of the boron-containing compound used for coordination with other lone pairs of electrons or conjugated electron donors in the raw material other than quantum dots is 900% of the mass of the quantum dots.

[0288] Embodiment 17

[0289] The process is carried out in accordance with Example 10, except that boron tribromide is used in step (2) instead of boric acid, and the amount used remains unchanged.

[0290] Embodiment 18

[0291] The process is carried out in accordance with Example 10, except that 4-methylphenylboric acid is used in place of boric acid in step (2), and the amount used remains unchanged.

[0292] Embodiment 19

[0293] The process is carried out in accordance with Example 10, except that in step (2), 3-carboxypropylboric acid is used instead of boric acid, and the amount used remains unchanged.

[0294] Embodiment 20

[0295] The process is carried out in accordance with Example 10, except that 4-bromobutylboric acid is used in place of boric acid in step (2) in an unchanged amount.

[0296] Embodiment 21

[0297] The process is carried out in accordance with Example 10, except that hydroxypropyl boric acid is used in step (2) instead of boric acid, and the amount used remains unchanged.

[0298] Embodiment 22

[0299] The process is carried out in accordance with Example 10, except that diethyl borate is used in place of boric acid in step (2) in an unchanged amount.

[0300] Embodiment 23

[0301] The same method is carried out as in Example 10, except that phenylboronic acid monoethyl ester is used in step (2) instead of boric acid, and the amount used remains unchanged.

[0302] Embodiment 24

[0303] The process is carried out in accordance with Example 10, except that 4-trifluoromethylphenylboric acid is used in place of boric acid in step (2), and the amount used remains unchanged.

[0304] Embodiment 25

[0305] The process is carried out in accordance with Example 10, except that in step (2), B,B-di(4-fluorophenyl)boric acid is used instead of boric acid, and the amount used remains unchanged.

[0306] Embodiment 26

[0307] The process is carried out in accordance with Example 10, except that 3-formylphenylboronic acid is used in step (2) instead of boric acid, and the amount used remains unchanged.

[0308] Embodiment 27

[0309] The process is carried out in accordance with Example 10, except that 4-carboxyphenylboric acid is used in place of boric acid in step (2), and the amount used remains unchanged.

[0310] Comparative Example 7

[0311] The same method is used as in Example 10, except that the type of quantum dots is the same, the total amount is unchanged, but no boron-containing compound is added. Specifically, in step (2), only 1 kg of antioxidant 1076, 0.5 kg of light stabilizer 123, and 48.5 kg of PS pellets are added, mixed and stirred evenly, and then extruded and granulated to obtain auxiliary agent pellets, which are set aside.

[0312] Comparative Example 8

[0313] The method is carried out in accordance with Example 10, except that the type of quantum dots is the same and the total amount is unchanged, but thiolate and phosphate are used instead of the boron-containing compound. Specifically, in step (2), 0.5 kg of octanethiol zinc salt, 0.5 kg of dodecylphosphonic acid zinc salt, 1 kg of antioxidant 1076, 0.5 kg of light stabilizer 123, and 47.5 kg of PS pellets are mixed and stirred evenly, and then extruded and granulated to obtain auxiliary agent pellets, which are set aside.

[0314] Comparative Example 11

[0315] The method is carried out in accordance with Example 10, except that the proportion of BX covalent bonds and BX coordination bonds is controlled to reach the proportion described in Table 5. To meet the change in the condition, the following adjustments are required: the amount of the boron compound used in step (2) is reduced. Step (2) is as follows: 0.03 kg of boric acid, 0.03 kg of dodecylboric acid, 1 kg of antioxidant 1076, 0.5 kg of light stabilizer 123, and 48.44 kg of PS pellets are mixed and stirred evenly, and then extruded and granulated to obtain auxiliary agent pellets, which are set aside.

[0316] The products of the above-mentioned embodiments and comparative examples were subjected to corresponding absorption spectra (nuclear magnetic resonance 11 B spectrum) test, the test results show that the groups in the corresponding formula 1 of the tri-coordinate boron-containing quantum dot complex and the corresponding formula 2 of the tetra-coordinate boron-containing quantum dot complex contained in the product are shown in Table 3-1 and Table 3-2 respectively, where only the most basic structure of the corresponding general formula is written here, excluding the derivative form. The product is chain-shaped, n1 and n2 are natural numbers, and n1 and n2 are calculated based on the theoretical value of the feed.

[0317] Table 3-1 Chemical structures of tri-ligand boron-containing quantum dot complexes

[0318]

[0319] Table 3-2 Chemical structures of tetraligand boron-containing quantum dot complexes

[0320]

[0321] Test Example 2

[0322] Taking Comparative Examples 7-8 and Examples 10-12 as examples, the quantum dot PS optical diffuser plates prepared by the corresponding production lines of the examples were subjected to aging tests. The test conditions were 85°C, 90% RH, 800 W / m 2 Blue light irradiance (blue light wavelength is 450 nm), the aging process test time is generally 100-200h, and the color coordinates x, y, and brightness Lv value of the quantum dot PS optical diffuser are measured using a color analyzer. The results are shown in Figure 3 (change of color coordinate x), Figure 4 (Change of color coordinate y), Figure 5 (Changes in brightness Lv value).

[0323] The same aging test as above was performed on Examples 13-16, and the test results of the initial values ​​before aging and the last aging of Examples 13-16 and Comparative Example 8 are shown in Table 4. Among them, Δx and Δy are the difference between the color coordinate X value after aging and the color coordinate X value before aging, and the difference between the color coordinate Y value after aging and the color coordinate Y value before aging, respectively. If there is a decrease, Δx and Δy are negative values; ΔLv% is calculated as (brightness Lv value after aging-brightness Lv value before aging) / brightness Lv value before aging.

[0324] Table 4

[0325]

[0326] above Figure 3-5 The data in Table 4 show that: the embodiments of the present invention use an appropriate amount of boron-containing compounds to prepare quantum dot optical diffuser plates, which have good heat resistance and achieve the coating of quantum dots by boron-containing compounds during the extrusion process; compared with the prior art (without boron compounds), the present invention significantly improves the stability of the quantum dot optical diffuser plate and ensures excellent optical properties. Among them, the optical properties and stability of Examples 13 / 14 / 15 / 16 are basically comparable to those of Example 10, among which Example 13 is slightly worse than Example 10, and the optical properties and stability effects of Examples 14 / 15 / 16 gradually become better.

[0327] Test Example 3

[0328] For the quantum dot PS optical diffuser plates prepared by the corresponding production lines of the above comparative examples and embodiments, ICP-OES was used to measure the B element of different quantum dot diffuser plates. The results are shown in Table 5.

[0329] The density of black and yellow spots on the board surface was measured by the same method as in Test Example 1, and the results are shown in Table 5. The density of black and yellow spots on the board surface in the subsequent tables is represented by "β".

[0330] and by molecular absorption spectroscopy (NMR 11B spectrum) detects the ratio of BX covalent bonds and BX coordination bonds in the quantum dot PS optical diffuser of each example, and the results are shown in Table 5.

[0331] Table 5

[0332]

[0333] above Figure 3-5 The data in Tables 4-5 show that the quantum dot optical diffuser plate prepared by the embodiment of the present invention has good heat resistance by using an appropriate amount of boron-containing compounds, which significantly improves the stability of the quantum dot optical diffuser plate, ensures excellent optical properties, and effectively avoids the appearance of black and yellow spots.

[0334] Furthermore, it can be seen from the data in Examples 10 and 13-16 and Tables 4 and 5 that the stability of the quantum dot optical diffuser plate in the embodiments of the present invention is positively correlated with the amount of the boron-containing compound (the mass content of the boron element). When the boron content is within an appropriate range, the stability gradually increases, which fully demonstrates the protection of the optical properties of the quantum dots by the boron-containing compound.

[0335] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A boron-containing quantum dot complex aggregate, characterized in that: The invention comprises a tri-coordinate boron-containing quantum dot complex and a tetra-coordinate boron-containing quantum dot complex formed by chemical bonding of a boron-containing compound and a quantum dot, wherein the boron-containing compound in the tri-coordinate boron-containing quantum dot complex is covalently bonded to the quantum dot, and the boron-containing compound in the tetra-coordinate boron-containing quantum dot complex is coordination-bonded to the quantum dot, and the proportion of XB coordination bonds in the aggregate of the boron-containing quantum dot complex to the sum of the number of XB covalent bonds and XB coordination bonds is 2%-50%, and X is selected from X1, X2, X3, X4, X5, and X6; wherein the chemical general formula of the tri-coordinate boron-containing quantum dot complex is as shown in the following formula 1, and the chemical general formula of the tetra-coordinate boron-containing quantum dot complex is as shown in the following formula 2; Formula 1; Formula 2; Wherein, QD is quantum dot; R8, R9, R 10 , R 11 , R 12 , R 13 Each of them is independently selected from alkoxy, hydrocarbon, substituted hydrocarbon, halogen, carboxyl, hydroxyl, aldehyde, ester and amide, and the substituent in the substituted hydrocarbon is selected from at least one of halogen, hydroxyl, alkoxy, carboxyl, aldehyde, ester and amide; n1=natural number, n2=natural number; X1, X2, X3, X4, X5 and X6 are each independently selected from VIA group elements, VA group elements and IVA group elements.

2. The boron-containing quantum dot complex aggregate according to claim 1, characterized in that: The boron-containing quantum dot complex aggregate is a boron-containing quantum dot dispersion, and the content of boron element in the boron-containing quantum dot dispersion is 1000ppm-9000ppm.

3. The boron-containing quantum dot complex aggregate according to claim 1, characterized in that: The boron-containing quantum dot composite aggregate is a boron-containing quantum dot composite plate, and the content of boron element in the boron-containing quantum dot composite plate is 13ppm-1750ppm.

4. The boron-containing quantum dot complex aggregate according to claim 1, characterized in that: X1, X2, X3, X4, X5, and X6 are each independently selected from O, S, Se, Te, N, P, As, C, Si, and Ge.

5. The boron-containing quantum dot complex aggregate according to claim 1, characterized in that: R8, R9, R 10 , R 11 , R 12 , R 13 Each of them is independently selected from an alkoxy group having 1-18 carbon atoms, a hydrocarbon group having 1-18 carbon atoms, a substituted hydrocarbon group having 1-18 carbon atoms, a halogen, a carboxyl group, a hydroxyl group, an aldehyde group, an ester group, and an amide group; the hydrocarbon group having 1-18 carbon atoms is selected from an alkyl group having 1-18 carbon atoms, an aryl group having 6-18 carbon atoms, an alkenyl group having 2-18 carbon atoms, and an alkynyl group having 2-18 carbon atoms.

6. The boron-containing quantum dot complex aggregate according to claim 1 or 5, characterized in that: R8, R9, R 10 , R 11 , R 12 , R 13 Each is independently selected from an alkoxy group having 1 to 18 carbon atoms, an alkyl group having 1 to 18 carbon atoms, an aryl group or a substituted aryl group having 6 to 18 carbon atoms, and a hydroxyl group; The substituent group in the substituted aryl group having 6 to 18 carbon atoms is selected from at least one of an alkyl group, a halogen group, a hydroxyalkyl group, an alkoxy group, a halogen group, a carboxyl group, and an aldehyde group.

7. The boron-containing quantum dot complex aggregate according to claim 1, characterized in that: The quantum dots are of a bare core structure, and the surface of the bare core structure has at least one of Group IVA atoms, Group VA anions, and Group VIA anions.

8. The boron-containing quantum dot complex aggregate according to claim 1, characterized in that: The quantum dots are of a core-shell structure, and the shell surface of the core-shell structure contains at least one of IVA group atoms, VA group anions, and VIA group anions.

9. A method for preparing a boron-containing quantum dot dispersion, characterized in that: The steps include: S1. Prepare a boron-containing compound and a dispersing solvent; S2, adding quantum dots into a system of boron-containing compounds and a dispersing solvent and introducing an inert gas; S3, heating, mixing and dispersing the system obtained in S2, and keeping the temperature for reaction; during the reaction, the boron-containing compound reacts with the quantum dots to form a tri-coordinate boron-containing quantum dot complex and a tetra-coordinate boron-containing quantum dot complex, the boron-containing compound in the tri-coordinate boron-containing quantum dot complex is covalently bonded to the quantum dots, and the boron-containing compound in the tetra-coordinate boron-containing quantum dot complex is coordination-bonded to the quantum dots, the proportion of XB coordination bonds in the boron-containing quantum dot dispersion to the sum of the number of XB covalent bonds and XB coordination bonds is 2%-50%, and X is selected from X1, X2, X3, X4, X5, and X6; S4, cooling; In S3, the chemical formula of the tri-coordinate boron-containing quantum dot complex is as shown in the following formula 1, and the chemical formula of the tetra-coordinate boron-containing quantum dot complex is as shown in the following formula 2; Formula 1; Formula 2; Wherein, QD is quantum dot; R8, R9, R 10 , R 11 , R 12 , R 13 Each of them is independently selected from alkoxy, hydrocarbon, substituted hydrocarbon, halogen, carboxyl, hydroxyl, aldehyde, ester and amide, the substituent in the substituted hydrocarbon is selected from at least one of halogen, hydroxyl, alkoxy, carboxyl, aldehyde, ester and amide, n1=natural number, n2=natural number, X1, X2, X3, X4, X5 and X6 are each independently selected from VIA group elements, VA group elements and IVA group elements.

10. The method for preparing a boron-containing quantum dot dispersion according to claim 9, characterized in that: The content of boron element in the boron-containing quantum dot dispersion is 1000ppm-9000ppm.

11. The method for preparing a boron-containing quantum dot dispersion according to claim 9, characterized in that: In S2, the mass ratio of quantum dots to boron-containing compounds is 1:0.25-5, and / or, the mass ratio of boron-containing compounds to dispersing solvent in S1 is 0.01-0.5:

1.

12. The method for preparing a boron-containing quantum dot dispersion according to claim 9, characterized in that: The dispersing solvent in S1 includes at least one of alkanes, aromatic hydrocarbons, organic amines, octadecene, organic carboxylic acids containing 1 to 18 carbon atoms, liquid paraffin, acrylates, organic silanes, and organic phosphines; and / or, The reaction temperature of the heat preservation reaction in S3 is higher than the melting point of the system of the boron-containing compound and the dispersion solvent, and lower than the boiling point of the system of the boron-containing compound and the dispersion solvent. The reaction time is 0.1h-3h, and the stirring speed of the mixed dispersion is 100 rpm-300 rpm.

13. The method for preparing a boron-containing quantum dot dispersion according to claim 9, characterized in that: When the proportion of covalent bonds needs to be increased, the reaction temperature in S3 is controlled to be 100°C-300°C; when the proportion of coordination bonds needs to be increased, the reaction temperature in S3 is controlled to be 30°C-100°C and not equal to 100°C.

14. The method for preparing a boron-containing quantum dot dispersion according to claim 9, characterized in that: The quantum dots are of a core-shell structure or a bare core structure, and exist in the form of a solid or a concentrated liquid. The mass fraction of the solid content of the quantum dots in the concentrated liquid is between 5% and 50%.

15. The method for preparing a boron-containing quantum dot dispersion according to claim 9, characterized in that: The boron-containing compound includes at least one of the corresponding compounds of the following three general formulae and their dehydration condensation, esterification, and amidation derivative compounds: General formula 1, , R1, R2, and R3 are each independently selected from a hydrocarbon group, an alkoxy group, a halogen group, and a substituted hydrocarbon group; General formula 2: , R4 and R5 are each independently selected from carboxyl, substituted hydrocarbon, halogen, hydrocarbon, alkoxy, and hydroxyl; General formula three: , R6 is selected from H or selected from hydrocarbon group, substituted hydrocarbon group, halogen, aldehyde group, carboxyl group, R7 is selected from hydrocarbon group, alkoxy group, hydroxyalkyl group, hydroxyl group; In the three general formulas, the substituents in the substituted hydrocarbon group are independently selected from at least one of halogen, hydroxyl, alkoxy, carboxyl, aldehyde, ester and amide.

16. The method for preparing a boron-containing quantum dot dispersion according to claim 15, characterized in that: The boron-containing compound comprises at least the general formula three; and / or, The number of carbon atoms in any carbon-containing group in Formula 1, Formula 2 and Formula 3 is less than 18, wherein the hydrocarbon group is selected from alkyl, aryl, alkenyl and alkynyl.

17. A boron-containing quantum dot dispersion, characterized in that: The boron-containing quantum dot dispersion is prepared by the method for preparing the boron-containing quantum dot dispersion as described in any one of claims 9 to 16.

18. A method for preparing a boron quantum dot composite plate, characterized in that: The steps include: S101, provide boron-containing compounds, quantum dot concentrates, polymer granules, and sheet functional additives; S102, mixing the quantum dot concentrate with at least part of the polymer pellets to obtain a quantum dot polymer mixture; S103, melt-extrude the quantum dot polymer mixture, the boron-containing compound, and the plate functional additive to form a boron-containing quantum dot composite plate; during the process, the boron-containing compound reacts with the quantum dots to form a tri-coordinate boron-containing quantum dot composite and a tetra-coordinate boron-containing quantum dot composite, the boron-containing compound in the tri-coordinate boron-containing quantum dot composite is covalently bonded to the quantum dots, and the boron-containing compound in the tetra-coordinate boron-containing quantum dot composite is coordination-bonded to the quantum dots, and the ratio of XB coordination bonds to the sum of the number of XB covalent bonds and XB coordination bonds in the boron-containing quantum dot composite plate is 2%-50%, and X is selected from X1, X2, X3, X4, X5, and X6; In S103, the chemical formula of the tri-coordinate boron-containing quantum dot complex is as shown in the following formula 1, and the chemical formula of the tetra-coordinate boron-containing quantum dot complex is as shown in the following formula 2; Formula 1; Formula 2; Wherein, QD is quantum dot; R8, R9, R 10 , R 11 , R 12 , R 13 Each of them is independently selected from alkoxy, hydrocarbon, substituted hydrocarbon, halogen, carboxyl, hydroxyl, aldehyde, ester and amide, the substituent in the substituted hydrocarbon is selected from at least one of halogen, hydroxyl, alkoxy, carboxyl, aldehyde, ester and amide, n1=natural number, n2=natural number, X1, X2, X3, X4, X5 and X6 are each independently selected from VIA group elements, VA group elements and IVA group elements.

19. The method for preparing a boron-containing quantum dot composite plate according to claim 18, characterized in that: The content of boron in the boron quantum dot composite plate is 13ppm-1750ppm; and / or, The mass ratio of quantum dots to the total amount of boron-containing compounds is 1:0.5-40, and the mass of the boron-containing compounds used for coordination and bonding with other lone pairs of electrons or conjugated electron donors in the raw materials except quantum dots is 1.2%-1000% of the mass of the quantum dots.

20. The method for preparing a boron-containing quantum dot composite plate according to claim 18, characterized in that: The melt extrusion process of S103 includes: subjecting the boron-containing compound, antioxidant, light stabilizer and another part of polymer pellets to a second mixed extrusion to obtain auxiliary agent pellets; then feeding the quantum dot polymer mixture and the auxiliary agent pellets into a first extruder, and feeding the diffusant and toughening agent into a second extruder and a third extruder respectively, and then performing melt extrusion; wherein the temperature of the second mixed extrusion is 180°C-220°C.

21. The method for preparing a boron-containing quantum dot composite plate according to claim 18, characterized in that: The melt extrusion conditions in S103 include: a processing temperature of 210° C. to 270° C. and a reaction time of 1 to 2 min; And / or, the stirring speed of the first mixing in S102 is 300-700 rpm.

22. The method for preparing a boron-containing quantum dot composite plate according to claim 18, characterized in that: The boron-containing quantum dot composite plate is a boron-containing quantum dot optical diffusion plate, and the corresponding plate functional additives include at least one of an antioxidant, a light diffuser, a toughening agent, and a light stabilizer; the quantum dots include red quantum dots and / or green quantum dots, and the polymer particles are selected from polystyrene, polymethyl methacrylate, polycarbonate, polyethylene, and polypropylene; wherein, The thickness of the boron quantum dot composite plate is 1.2 mm-3.0 mm; and / or, In S101, based on the total amount of raw materials, the mass fraction of boron-containing compounds is 0.05%-1%, the mass fraction of quantum dot concentrate is 0.05%-0.2%, the mass fraction of quantum dots in the quantum dot concentrate is 5%-50%, the mass fraction of antioxidant is 0.1%-2%, the total mass fraction of light diffuser and toughening agent is 0.5%-2%, and the mass fraction of light stabilizer is 0.05%-2%.

23. The method for preparing a boron-containing quantum dot composite plate according to claim 18, characterized in that: The boron-containing compound includes at least one of the corresponding compounds of the following three general formulae and their dehydration condensation, esterification, and amidation derivative compounds: General formula 1, , R1, R2, and R3 are each independently selected from a hydrocarbon group, an alkoxy group, a halogen group, and a substituted hydrocarbon group; General formula 2: , R4 and R5 are each independently selected from carboxyl, substituted hydrocarbon, halogen, hydrocarbon, alkoxy, and hydroxyl; General formula three: , R6 is selected from H or selected from hydrocarbon group, substituted hydrocarbon group, halogen, aldehyde group, carboxyl group, R7 is selected from hydrocarbon group, alkoxy group, hydroxyalkyl group, hydroxyl group; In the three general formulas, the substituents in the substituted hydrocarbon group are independently selected from at least one of halogen, hydroxyl, alkoxy, carboxyl, aldehyde, ester and amide.

24. The method for preparing a boron-containing quantum dot composite plate according to claim 23, characterized in that: The boron-containing compound comprises at least the general formula three; and / or, The number of carbon atoms in any carbon-containing group in Formula 1, Formula 2 and Formula 3 is less than 18, wherein the hydrocarbon group is selected from alkyl, aryl, alkenyl and alkynyl.

25. A boron quantum dot composite plate, characterized in that: The composite plate is prepared by the method for preparing a boron-containing quantum dot composite plate as described in any one of claims 18 to 24.

26. Use of the boron-containing quantum dot complex aggregate according to any one of claims 1 to 8 in a quantum dot diffusion plate, a quantum dot light-converting agricultural film, a quantum dot on-chip package, and a quantum dot electroluminescent device.

Citation Information

Patent Citations

  • Quantum dot, preparation method of quantum dot ligand, modification method of quantum dot and photoelectric device

    CN110205111A

  • Quantum dot composite material and preparation method thereof

    CN112480927A

  • Small molecule passivation of quantum dots for increased quantum yield

    CN113366083A

  • Methods to improve the quantum yield of indium phosphide quantum dots

    CN113710773A

  • Core-shell nanostructures comprising zinc halides and zinc carboxylates bound to surface

    CN114341312A